The Relationship between Verbal Ability and Mathematical Communication Ability to Build Non-curved Space - Fhela Vhantoria Ningrum; Fajar Husaini; Yulina; Muinah (Universitas Cokroaminoto Palopo, 2024)
The learning outcomes of low non-curved geometric shapes are directly proportional to the low level of mathematical communication skills of non-curved geometric shapes. Apart from that, verbal ability is low if students are given questions that have different words in sentences from the previous practice questions, so they have difficulty solving the questions research aims to see the relationship between verbal abilities and Mathematical Communication Skills Build non-curved spaces. This Quantitative research method Correlational technique with variables verbal ability (X) and Mathematical Communication Skills Build non-curved spaces (Y). The research population was all students in class VIII SMPN & Kotabumi with a sample of 24 people. The results of the correlation analysis of verbal ability (X) with Mathematical Communication Skills Build non-curved spaces (Y) produced a correlation coefficient of rhitung 0.57 with rtabel = 0.40. Based on the calculation results, the value obtained is rhitung = 0.57 > rtabel = 0.40 so that H0 is rejected. This shows that there is a relationship between verbal ability and Mathematical Communication Skills Build non-curved spaces for class VIII SMP Negeri 7 Kotabumi North Lampung for the 2022/2023 academic year